Os impactos dos conflitos políticos na gestão dos recursos oriundos das concessões florestais no município de Oriximiná - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This research deals with the management of resources originating from forest concessions in the municipality of Oriximiná, in the state of Pará, focusing on the impacts caused by political and interest-related conflicts. The management of concession resources directly affects traditional communities living around the Saracá-Taquera National Forest (Flona Saracá-Taquera). Furthermore, it is important to fill the existing gap in the literature on this topic. In this context, the research seeks to answer the following question: what are the impacts of political and interest-related conflicts on the management of resources originating from forest concessions in the municipality of Oriximiná? Thus, the general objective is to analyze and discuss the impacts of political and interest-related conflicts on the management of resources from forest concessions in the municipality of Oriximiná and the effects on the transfers related to the forest concession, with specific objectives: a) to contextualize the implementation of the forest concession in the municipality of Oriximiná; b) to conduct a quantitative survey of the resources related to the forest concession allocated to the municipality; and c) to carry out a critical analysis of the political and interest-related conflicts associated with the management of resources from the forest concession in Oriximiná. The research is characterized as a case study with a qualitative approach, using as main methodological procedures the documental analysis, bibliographic research, semi-structured interviews with local actors involved in the resource management, and content analysis. The results point to institutional, political, and administrative obstacles, with centralized decisions, lack of transparency, fragility of the COMDEMA, low community participation, and absence of participatory planning.
Keywords: Concessão Florestal; Gestão de Recursos; Conflitos Políticos; CNPQ:: CIÊNCIAS HUMANAS